Analisis Bakteri Entero Toksigenic Escherichia Coli ( ETEC) Dengan Metode (BGLB) Pada Depot Air Minum Isi Ulang Di Pemukiman Kumuh. - Rapael Ginting (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2020)
Based on research conducted at the drinking water depot in Mabar Medan Deli and Medan City Environmental Health Engineering Laboratory (negative) in drinking water, it is declared not contaminated with ecoli, while if the results of the AMIU quality inspection are> 0 in 100 ml samples (positive) in drinking water, then the calculation results are obtained with a p-value (0.001 <0.005) then Ha is accepted and Ho rejected so that the BGLB method is effective against the examination of Escherichia Coli bacteria contamination in the refill drinking water depot. It is stated that it is contaminated with ecoli. This research was in an observational form, using a cross-sectional approach.